A bibliometric review of architecture research in GCC countries: An analysis based on the web of science - Zami, Mohammad Sharif; Rahaman, Md Safiqur (Qualitative and Quantitative Methods in Libraries; Vol 11 No 1 (2022): March issue 2022, 2022)
Purpose: A number of studies concluded that the assumption about research established in architecture schools is dominated by myth, and research is not taken to analyze, assess, and evolve a new thought and technology. This mythological assumption significantly affected the research output of the architecture discipline globally. In order to mitigate low research yield from the field of architecture, it is essential to carry out a bibliometric investigation to assess the situation on the ground. This study aims to explore the scientific research (during 1976 – 2020) outcomes in the area of architecture in Gulf Cooperation Council (GCC) countries to explore research productivity and highlight the trends and tendencies besides assessing the gaps to execute future research. Design/Methodology/Approach: An extensive bibliometric method has been implied in published research of GCC to guide researchers in the field of architecture. The research data were retrieved from the web of science and analyses with the help of bibliometric software such as VOSviewer, Bibexcel, and Biblioshiny. Findings: The findings show that 6 GCC countries contributed a total of 335 publications and 753 citations. 2019 contributed the highest research in architecture. The UAE was the most driving force with strong academic contribution (TP: 119), while Qatar was the most cited country (TC: 231). The topmost contributing intuition was Qatar University (TP: 41); Salama AM was the most prolific author and most cited author. KSA and Egypt had the most collaborative research work with 18 publications. While writing research papers, the authors of GCC mostly used the keywords such as architecture, sustainability, urban design, housing, urbanism, architectural design, architectural education, culture, heritage, Islamic architecture, urban planning, affordable housing, conservation, education, and energy efficiency.  Originality: This is the first comprehensive bibliometric analysis of architecture research produced by GCC countries.